Damage Simulation of Pre-Forming V-Neck Plates with Variations in Material Type, Time and Temperature Using the Taguchi Method - Avita Ayu Permanasari; Poppy Puspitasari; Kevin Valiant Cahya; Mahfud Ihsan (Universitas Negeri Malang, 2018)
In metal forming, damage can be caused by several factors: load on the workpiece, initial heating temperature, and temperature due to the friction between the die and the material for pre-forming. The metal forming process can be executed in 2 ways, namely by hot working and cold working. During these two types of mechanical working process, the metal undergoes plastic deformation. In hot working, the required deformation force is relatively low, and changes in mechanical properties are also insignificant. In cold working, a higher force is required, but the strength of the metal will increase significantly. The use of simulation has become increasingly widespread to predict and describe process mechanisms and optimize the pre-forming process. The study was conducted using a three-dimensional (3D) simulation to predict the effect of variations in time, material and temperature on the damage of pre-forming blocks. The simulation results showed that the greatest damage occurred after 0.006 s and at 25 °C to the specimen 1 (Aluminium 1xxx) with the highest damage value of 0.011833 which occurred. Specimen 7 (Aluminium 3xxx) had the lowest damage with the value of 0.011542 which occurred after 0.010 s and at 25 °C.